Malaria and Thrombocytopenia: A Systematic Review and Meta-Analysis - Halimah Ali Alawad et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Thrombocytopenia is a frequently reported hematological abnormality in malaria. However, its precise prevalence, diagnostic utility, and prognostic value across different Plasmodium species remain inadequately synthesized. To determine the pooled prevalence of thrombocytopenia in malaria, its accuracy in diagnosing malaria in febrile patients, and its association with severe disease and mortality. A systematic search of MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials was conducted from inception to May 2023. Observational studies (cohort, cross-sectional, case-control) reporting platelet counts or the prevalence of thrombocytopenia in patients with smear-positive or rapid diagnostic test (RDT)-confirmed malaria were included. Two independent reviewers extracted data on study characteristics, patient demographics, parasite species, platelet counts, and clinical outcomes. The quality of studies was assessed using the Newcastle-Ottawa Scale. 127 studies involving 98,451 malaria patients were included. The pooled prevalence of thrombocytopenia (platelet count <150,000/μL) was 74% (95% CI, 71-77%; I²=94%). Prevalence was high in both P. falciparum (72%, 95% CI 68-75%) and P. vivax (78%, 95% CI 74-81%) infections. The pooled mean platelet count was 89,500/μL (95% CI 85,200-93,800/μL). For diagnosing malaria in febrile patients, thrombocytopenia had a pooled sensitivity of 0.75 (95% CI 0.71-0.79), specificity of 0.81 (95% CI 0.77-0.84), and a diagnostic odds ratio of 14.2 (95% CI 10.5-19.1). Patients with severe thrombocytopenia (<50,000/μL) had a significantly higher risk of severe malaria (Pooled Relative Risk 3.45, 95% CI 2.68-4.44) and mortality (Pooled RR 2.91, 95% CI 1.98-4.27). Thrombocytopenia is a highly prevalent and salient feature of both P. falciparum and P. vivax malaria. It serves as a strong diagnostic marker for malaria in febrile illness and is a significant prognostic indicator for disease severity and mortality. Received Date: December 26, 2024 Accepted Date: January 12, 2024 Published Date: February 1, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/485